Pulpa y pergamino de café. VIII. Estudios básicos sobre la deshidratación de la pulpa de café - Molina, Mario Roberto; De la Fuente, Gabriel; Gudiel, Hugo; Bressani, Ricardo (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2025)
The drying curves obtained for coffee pulp indicated that pulp is an easy-to-dry material.It's moisture content was reduced from 85 to 6 per cent during the constant rate drying period. Experiments using the Van Arsdel analogue method and a traydrier with a counterflow arrangement showed that with an inlet air temperature of 75°C and a loading of 681 g/0.09 m2 (1.5 lb/fv2), a total drying area of 72 m2 was necessary to obtain a yield of 824 kg of dry material per 24 hours. Using a loading of 1,136 g/0.09 m2 (2.5 lb/fv2) and an inlet air temperature of 120°C yields of up to 477 kg of dry material per 24 hours were obtained with a drying area as small as 5.6 m2.The fact that coffee pulp is an easy-to-dry material, without any appreciable change in its chemical composition, is considered a great value to implement its use on a large scale basis.